Interesting Professionalism: Ethical and Aesthetic Dimensions in Barista Practice in Medan - Rossy Luckita Sasmita (PT ARFA DIGITAL TECHNOLOGY, 2026)
This study examines the professionalism of baristas in coffee shops in Medan city with a focus on the integration of the dimensions of service ethics and presentation aesthetics and their influence on customer satisfaction and loyalty. The aim of the study was to analyze the relationship between ethical practices, aesthetic presentation, and customer experience that influence loyalty in the context of tourism and hospitality. The methodology used is a mixed-method approach with an explanatory case study design, involving 15 baristas and 50 customers as samples. Data were collected through semi-structured interviews, questionnaire surveys, participatory observations, and visual documentation, then analyzed using SPSS for quantitative data and NVivo for qualitative data. The results showed that service ethics and presentation aesthetics were the dominant factors that increased customer satisfaction (score 4.4–4.5) and played a role as the main mediator of loyalty (80%). Qualitative findings support the quantitative results, showing that personal interactions, cleanliness, and interior design support the customer's multisensory experience. This research contributes to the literature on hospitality and service management as well as practical guidance for coffee shop managers to improve professionalism and customer loyalty.